1979
DOI: 10.1128/jb.140.2.620-633.1979
|View full text |Cite
|
Sign up to set email alerts
|

Regulated breakdown of Escherichia coli deoxyribonucleic acid during intraperiplasmic growth of Bdellovibrio bacteriovorus 109J

Abstract: During growth of Bdellovibrio bacteriovorus on [2-"C]deoxythymidine-labeled Escherichia coli, approximately 30% of the radioactivity was released to the culture fluid as nucleoside monophosphates and free bases; the remainder was incorporated by the bdellovibrio. By 60 min after bdellovibrio attack, when only 10% of the E. coli deoxyribonucleic acid (DNA) had been solubilized, the substrate cell DNA was degraded to 5 x 105-dalton fragments retained within the bdelloplast. Kinetic studies showed these fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Some host macromolecules, notably several outer membrane proteins (99), may be transferred intact from host to bdellovibrio, but most often host polymers are broken down to monomers at rates consistent with the synthetic needs of the parasite. For example, host DNA is split into 500-kilodalton pieces by an endonuclease, and then an exonuclease hydrolyzes off deoxyribonucleoside monophosphates which are incorporated directly into parasite DNA (259,351). Similar mechanisms probably exist for breakdown and resynthesis of RNA and protein (184).…”
Section: Modes Of Multiplicationmentioning
confidence: 99%
“…Some host macromolecules, notably several outer membrane proteins (99), may be transferred intact from host to bdellovibrio, but most often host polymers are broken down to monomers at rates consistent with the synthetic needs of the parasite. For example, host DNA is split into 500-kilodalton pieces by an endonuclease, and then an exonuclease hydrolyzes off deoxyribonucleoside monophosphates which are incorporated directly into parasite DNA (259,351). Similar mechanisms probably exist for breakdown and resynthesis of RNA and protein (184).…”
Section: Modes Of Multiplicationmentioning
confidence: 99%
“…It is actively motile and after adsorption onto the host, a specific enzyme(s) is induced in the parasite (Varon and Shilo, 1968). Maturation begins when the parasite penetrates through the outer membrane into the host periplasm where, -60 min later, synthesis of B. bacteriovorus DNA begins (Matin and Rittenberg, 1972; Rosson and Rittenberg, 1979). The parasite causes shut-off of the host macromolecular synthetic apparatus, and is able to grow on host cells killed by various agents, including antibiotics (Varon et al, 1969;Rittenberg and Shilo, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…occurs only in the host cell after invasion into the periplasmic space. Experiments with [3H]thymidine labelled E. coli showed that host DNA is degraded by bdellovibrio deoxyribonucleases and incorporated into bdellovibrio DNA [111,112]. Exogenous thymidine monophosphates compete effectively with labelled host DNA; low incorporation rates of thymidine argue for a deficiency of deoxynucleoside kinases [113].…”
Section: Proteobacteriamentioning
confidence: 99%